Equality within our lifetimes: how laws and policies can close—or widen—gender gaps in economies worldwide - Heymann, Jody (University of California Press, 2023)
A free ebook version of this title is available through Luminos, University of California Press’s Open Access publishing program. Visit www.luminosoa.org to learn more. Well into the twenty-first century, achieving gender equality in the economy remains unfinished business. Worldwide, women’s employment, income, and leadership opportunities lag men’s. Building and using a one-of-a-kind database that covers 193 countries, this book systematically analyzes how far we’ve come and how far we have to go in adopting evidence-based solutions to close the gaps. Spanning topics including girls’ education, employment discrimination of all kinds, sexual harassment, and caregiving needs across the life course, the authors bring the findings to life through global maps, stories of laws’ impact in courts and beyond, and case studies of making change. A powerful call to action, Equality within Our Lifetimes reveals how gender equality is both feasible and urgently needed to address some of the greatest challenges of our generation.